Samoa Education Management Information Systems : SABER Country Report 2015 - World Bank Group (World Bank, Washington, DC, 2016)
In 2011, the World Bank Group commenced a multiyear program designed to support countries in systematically examining and strengthening the performance of their education systems. Part of the World Bank’s new Education Sector Strategy, this evidence-based initiative, called SABER (Systems Approach for Better Education Results), uses diagnostic tools for examining education systems and their component policy domains against global standards and best practices and in comparison with the policies and practices of countries around the world. This report discusses the results of applying the SABER Education Management Information Systems (EMIS) tool in Samoa. The objectives of this report are to examine the system according to key policy areas, identify successes and challenges in the system, and provide recommendations to support the continued advancement of EMIS in Samoa. Samoa’s system is assessed in the following six policy areas: (1) legal framework, (2) organizational structure and institutionalized processes, (3) human resources, 4) infrastructural capacity, (5) budget, and (6) data-driven culture. To conclude, the Strengths, Weaknesses, Opportunities, and Threats (SWOT) profile (table 6) summarizes key points from the needs assessment and informs recommendations.